Prognostic value of circulating tumor cells in patients with non-small cell lung cancer: a Meta-analysis - Ming-Zhen LI; Shao-Hua HE; Ying-Hui JIN; Cheng CHEN; Si-Yu YAN; Yong-Bo WANG; Huan LIU; Zhi-Qing ZHOU; Han XIAO; Rui-Rui YANG; Li-Ming TAN (Yixue xinzhi zazhi)
Objective To systematically evaluate the prognostic value of circulating tumor cells (CTCs) in patients with non-small cell lung cancer (NSCLC).Methods We electronically searched CNIK, WanFang Data, CBM, VIP, PubMed, Web of Science, The Cochrane Library, and Embase database for literature regarding detection of baseline levels of CTCs and survival in NSCLC patients from inception to 28 September 2021. After screening for inclusion criteria, data extraction and quality assessment were performed followed by Meta-analysis using the RevMan 5.3 and Stata 15.0 software.Results 19 studies were included in this Meta-analysis with a total of 1,853 NSCLC patients. Meta-analysis revealed that NSCLC patients with high levels of CTCs had poorer progression-free survival (PFS) than those with low levels of CTCs [HR=2.49, 95% CI(1.50, 4.13), P=0.0004], but levels of CTCs had no significant predictive effect on overall survival (OS) [HR=1.18, 95%CI(0.70, 1.99), P=0.54].Conclusions Baseline CTCs levels have a significant predictive effect on PFS in NSCLC patients, but have no significant predictive ability on OS. This is an area which requires further study in the future.